Linguistic Roots of Surah At-Tariq: Structure and Morphological Significance - Al-Gharawi, Rana AbdelAziz (Journal of Arabic Language Sciences and Literature, 2025)
The Arabic language is distinguished by the richness of its morphological structures and the abundance of its word forms. Morphology is the key to understanding the meanings of these forms, as each morphological pattern is rooted in an original lexical root found in Arabic dictionaries. The main problem addressed in this study is the lack of a comprehensive analysis that combines the lexical root, morphological structure, and semantic meaning in Surah Al-Tariq. Previous studies have often treated these elements separately or focused on other surahs, which limited the understanding of their interactive relationship in this particular surah. Furthermore, the significant overlap between the lexical and morphological meanings in verbs and nouns calls for a detailed analysis to show how this relationship affects the Qur’anic meaning and reveals the specific semantic nuances that morphological structures acquire within the surah. This research aims to analyze the relationship between the lexical root, morphological structure, and semantic meaning in Surah Al-Tariq, and to study the harmony and challenges between lexical and morphological meanings, clarifying how their interaction influences the understanding of the Qur’anic text. The research adopts an inductive approach to identify the morphological forms, followed by a descriptive-analytical method to interpret them. The study covers the reasons for revelation, the name of the surah, definitions of key terms, and an applied analysis of verbs and nouns, linking them to their roots and meanings. The results show a strong correspondence between root, structure, and meaning, while highlighting unique semantic aspects in the surah’s context. The study recommends expanding research to other surahs for comparative analysis.